PERSEPSI KARYAWAN TERHADAP KUALITAS KELEMBAGAAN KAWASAN WISATA JUMIANG, KABUPATEN PAMEKASAN - Campina Illa Prihantini; Lutfiyanto Lutfiyanto (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2020)
The Jumiang tourism area is located in Pademawu Subdistrict, Pamekasan District, which is one of the tourism areas that can be built as educational tourism. This is based on natural conditions and the potential possessed by this tourism area. Since the tourism awareness group (pok-darwis) was formed, the tourist area of Jumiang is now making many improvements, especially in the availability of tourist facilities and attractions. This is aimed at attracting the number of tourists that declined in the past few years. The existence of Pok-Darwis is certainly the spearhead of the sustainability of the management of the Jumiang tourist area. This study uses qualitative analysis with a focus on institutional perception analysis. This analysis is expected to provide an evaluation to the relevant parties so that the management of Jumiang tourism area will be better so that the concept of sustainable tourism and education tourism can be achieved. The results of the analysis show that the institutional quality of Pok-Darwis for the Jumiang Tourism Area still has weaknesses, such as in terms of institutional strengthening. However, the institutional effectiveness of the Jumiang tourism area can be said to be effective.